2014
DOI: 10.1371/journal.pone.0084282
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Repetition of Self-Harm: A Systematic Review of Prospective Hospital-Based Studies

Abstract: BackgroundSelf-harm entails high costs to individuals and society in terms of suicide risk, morbidity and healthcare expenditure. Repetition of self-harm confers yet higher risk of suicide and risk assessment of self-harm patients forms a key component of the health care management of self-harm patients. To date, there has been no systematic review published which synthesises the extensive evidence on risk factors for repetition.ObjectiveThis review is intended to identify risk factors for prospective repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 77 publications
(108 reference statements)
8
104
5
Order By: Relevance
“…Previous systematic reviews on repetition of self-harm have: (i) focussed only on certain forms of self-harm (Fliege et al, 2009); (ii) included little or no data on potential neurocognitive factors (Mendez-Bustos et al, 2013); (iii) focussed only on psychometric tools in hospital (Randall et al, 2011); (iv) focussed only on hospital admissions (Larkin et al, 2014). As far as we are aware, there is no previous systematic review of the major neurocognitive factors and repetition of self-harm, inclusive of all forms of self-harm and all settings.…”
Section: Can We Use Neurocognition To Predict Repetition Of Self-harm?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews on repetition of self-harm have: (i) focussed only on certain forms of self-harm (Fliege et al, 2009); (ii) included little or no data on potential neurocognitive factors (Mendez-Bustos et al, 2013); (iii) focussed only on psychometric tools in hospital (Randall et al, 2011); (iv) focussed only on hospital admissions (Larkin et al, 2014). As far as we are aware, there is no previous systematic review of the major neurocognitive factors and repetition of self-harm, inclusive of all forms of self-harm and all settings.…”
Section: Can We Use Neurocognition To Predict Repetition Of Self-harm?mentioning
confidence: 99%
“…However, it was not able to be included because it classified "recent self-harm" as occurring within the last year, which was an exclusion criteria for the current review. Larkin and colleagues' systematic review of prospective hospital studies found that a few studies assessed autobiographical memory and overall there was a small association with repetition of self-harm (Larkin et al, 2014). There may also be other important aspects of memory: Martinez-Aran determined that impairments of verbal memory (on the California Verbal Learning Test) were correlated with the number of suicide attempts in secondary analyses (Martinez-Aran et al, 2004).…”
Section: Memory Processingmentioning
confidence: 99%
“…In a recent international review of case-control and cohort studies, hopelessness was found to be associated with a greater than twofold increase in risk of suicide amongst people with depression (Hawton et al, 2013). However, prospective, hospital-based studies of self-harm have tended to examine risk factors in isolation, overlooking their cumulative effect (Larkin et al, 2014). Their inclusion could enhance understanding of some existing known risk factors (Kessler et al, 1999;Larkin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, prospective, hospital-based studies of self-harm have tended to examine risk factors in isolation, overlooking their cumulative effect (Larkin et al, 2014). Their inclusion could enhance understanding of some existing known risk factors (Kessler et al, 1999;Larkin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] A recent study found that premature, alcohol-related deaths were nine times more likely among those who engage in self-harm compared to the general population. [3] Furthermore, acute alcohol consumption is linked to impulsive suicidal behaviours.…”
Section: Introductionmentioning
confidence: 99%